A long-term multi-region load-dispatch model based on grid structures for the optimal planning of China's power sector. (12th July 2017) - Guo, Zheng; Ma, Linwei; Liu, Pei; Jones, Ian; Li, Zheng
Highlights: A long-term multi-region load-dispatch grid-structure-based model is developed based on previous work. A most-likely scenario is performed considering currently available technologies and clean energy policies. Results indicate significant influences of transmission facilities on regional power generation profiles. Clean energy targets contribute greatly to the deployment of wind and PV and the reduction of carbon emissions. CCS may need to be implemented for carbon restriction in the long term owing to limited renewable resources. Abstract: China's power sector has experienced rapid development over the past decade. With the clean energy targets and carbon mitigation objectives proposed by the government as well as rapid development of power transmission infrastructure, future potential pathways for the expansion of China's power sector are worth assessing. In this paper, a mathematical model, named the Long-term Multi-region Load-dispatch Grid-structure-based (LoMLoG) has been developed and a "most-likely" scenario has been created that delivers insights into optimal regional power generation, transmission and emissions profiles. The results confirm the importance of clean energy targets in driving deployment of renewable energy and maximizing its contribution to carbon mitigation of China's power sector. In addition, the development of power transmission infrastructure will significantly influence regional power generation and transmission profiles. Last but not least, carbon mitigation approaches in the long term are discussed, and rational methods of allocating future carbon caps are presented.